The impact of randomness on high speed wireless campus network in IEEE802.11e - Alam, M.K.; Abd Latif, Suhaimi; Akter, Mahmuda; Masud, M. H.; Hakak, Saqib Iqbal; Khan, M.N.H; Anwar, Farhat (2014)
The enhancement of channel access mechanism assures to provide Quality of Service (QoS) using the service differentiation mechanism over WLAN in IEEE802.11e. The service differentiation scheme is used in the Enhanced Distributed Channel Access (EDCA) MAC layer protocol and this protocol is used the random back-off window algorithm to provide QoS for the real time multimedia applications. However, the back-off window mechanism ensures QoS to satisfy multimedia traffic but it only the probabilistic QoS due to the random nature of the algorithm. As like as the randomness of the mobility models that can be reduced the network performance. In this paper, we analyze the proposed network performance based on the variation of randomness using different seed values and evaluate the network performance using various performance metrics in IEEE802.11e.